ANALISIS INSTALASI PEMASANGAN KABEL FIBER OPTIK DI PT. CANDI KEYNATECH UTAMA DAN PENERAPANNYA PADA MATA KULIAH KABEL DAN TEKNIK PEMASANGAN PADA PROGRAM STUDI S1 PENDIDIKAN TEKNIK ELEKTRO - Imansyah, Syahrul; Nyoman Santiyadnya; Wayan Mahardika Prasetya Wiratama (Jurnal Pendidikan Teknik Elektro Undiksha, 2025)
This research aims to find out the components used in Fiber Optic Cable Installation in the Cable and Project-Based Installation Techniques Course, to find out the process of Fiber Optic Cable Installation in the Project-Based Cable and Installation Techniques Course, and to find out whether the signal produced is good. This research uses a qualitative and quantitative approach with a case study design. This research was conducted at PT. Main Keynatech Temple. The research results show that effective fiber optic cable installation techniques require the use of appropriate tools, strict quality monitoring, and good planning. The hypothesis of this research is as follows. 1) After conducting an interview, the components used in Fiber Optic Cable Installation in the Cable and Installation Techniques Course are Splicers, Millers, Cleavers, OTDRs, and other Installation Devices. 2) The Fiber Optic Cable Installation Process in the Cable and Installation Techniques Course can run well. 3) By using the OPM tool the resulting signal quality is good.